Characteristics of sagittal spine alignment in female patients with distal radius fractures due to fall. Issue 8 (August 2020) - Kaneko, Ayaka; Naito, Kiyohito; Nagura, Nana; Obata, Hiroyuki; Goto, Kenji; Sugiyama, Yoichi; Koike, Masato; Nojiri, Hidetoshi; Iwase, Yoshiyuki; Kaneko, Kazuo
Abstract: Objectives: Distal radius fractures occur due to reflex clasp when falling. Recently, attention has been focused on the strong relationship between sagittal spine alignment and falls. Therefore, we investigated the parameters of sagittal spinal alignment in distal radius fractures in female patients. Patients and methods: The subjects were group D: 28 female patients with distal radius fractures aged 50 years or older (mean age: 69.3 years), and group C: 26 healthy female patients without a history of fragility fractures (mean age: 70.5 years). Height, body weight, and body mass index (BMI) were measured as physical indices. As parameters of sagittal spinal alignment, the sagittal vertical axis (SVA), pelvic tilt (PT), pelvic incidence (PI), sacral slope (SS), lumber lordosis (LL), and thoracic kyphosis (TK) were measured on lateral whole-spine plain radiographs in a standing position. The measured physical indices and sagittal spinal alignment parameters were compared between groups. Results: Height, weight, and BMI did not differ significantly between the two groups. Among the sagittal spinal alignment parameters, PT, PI, SS, LL, and TK did not differ significantly between groups, whereas SVA was significantly higher in group D than in group C (P < 0.05). Conclusion: In this study, SVA was significantly higher in group D than in group C. As SVA increased, the center of gravity of the body shifts forward, which can cause the body to lose balance and fall. This study suggested that an increase in SVA is associated with distal radius fractures. Abstract : Emergency medicine, Medical imaging, Metabolism, Public health, Rehabilitation; Surgery; Biomechanics; Aging; Orthopedics; Trauma; Aging and life course; Distal radius fractures; Spinal sagittal balance; Sagittal vertical axis; Fall.